Occupational health risks of workers in the metallurgical industry - Sharavara, L. P.; Шаравара, Лариса Павлівна (My University, 2020)
Occupational activity is known to be associated with the possibility of developing occupational diseases under the influence on the workers’ organism of adverse factors of the production environment and the labor process. From the standpoint of occupational medicine, ferrous metallurgy is characterized by the presence of numerous sources of occupational hazards: dust, gaseous toxic substances, radiant and convective heat, noise, vibration, electromagnetic and magnetic fields, high severity and intensity of work. The aim of the study. Assess occupational risks to the health of workers employed in the metallurgical industry.